A novel method for the synthesis of BiOCl/Bi2Sn2O7 heterojunction photocatalysts with enhanced visible light photocatalytic properties. (16th August 2016) - Lv, Dongdong; Zhang, Dafeng; Sun, Qinzhao; Wu, Jiandong; Zhang, Li; Pu, Xipeng; Ma, Huiyan; Dou, Jianmin
Abstract: A novel simple method was proposed to synthesize BiOCl/Bi2 Sn2 O7 heterojunction photocatalysts through the treatment of Bi2 Sn2 O7 with HCl solution of different concentrations. The as-synthesized photocatalysts were characterized by x-ray diffraction, scanning electron microscopy, transmission electron microscopy, photoluminescence, x-ray photoelectron spectroscopy and ultraviolet–visible diffuse reflectance spectroscopy. The experimental results show that sheet-like BiOCl particles were obtained after the HCl treatment. Bi2 Sn2 O7 nanoparticles were distributed on the BiOCl sheets, resulting in the low aggregation of the Bi2 Sn2 O7 nanoparticles. As compared to BiOCl and Bi2 Sn2 O7, BiOCl/Bi2 Sn2 O7 showed enhanced photocatalytic activity under visible light irradiation, which can be attributed to the effective separation of photogenerated electrons and holes due to the formation of a BiOCl/Bi2 Sn2 O7 heterojunction. In addition, the dominant active species and the photocatalytic mechanism were discussed in detail.